Tissue engineered corneal endothelium transplantation in an ex vivo human cornea organ culture model - Meng-Chen Tsai; Alvena Kureshi; Julie T. Daniels (Scientific Reports)
Abstract Transplantation of corneal tissue is the standard treatment for irreversible corneal endothelium decompensation by replacing the malfunctioning corneal endothelial cells and Descemet’s membrane. However, this surgery depends on limited donor tissue supply. Thus, developing suitable alternatives for donor grafting material through a tissue engineering approach is needed to enable the transplantation of cultured endothelial cells to restore normal endothelial function. Here, we proposed using a plastic compressed collagen 3D matrix called Real Architecture For 3D Tissues (RAFT) as a scaffold for cell culture. The porcine cornea endothelial cells (PCECs) were seeded on RAFT to construct a tissue-engineered corneal endothelium. Then, the porcine cell-seeded-RAFT graft was transplanted onto a human cornea and maintained in an ex vivo organ culture model. The results showed that PCECs formed a high-density monolayer on RAFT expressing endothelial cell markers, ZO-1, Na/K ATPase and N-cadherin. More importantly, the cell-seeded RAFT transplantation successfully restored corneal endothelium function, drawing the thickness of endothelium-wounded cornea back to normal in two weeks of the ex vivo human cornea organ culture.